Evaluation of the chemical composition and antioxidant activity of Citrus limon essential oil and its application in margarine preservation - Louiza HIMED; Salah Merniz; Malika Barkat (Algerian Journal of Natural Products, 2016)
Essential oils are aromatic oil liquids obtained from various plant parts. The growing interest in the substitution of synthetic antioxidant agents by natural ones has fostered research on vegetable sources and the screening of plant materials in order to identify new compounds. The study aims to evaluate the use of essential oil extract by cold pression of Citrus limon (Lisbon variety) as a substitute of Tocoblend (mixture of α, β, γ and δ-tocopherol) used as antioxidant in margarine preservation. The major constituents of the essential oil extract Identified were Limonene (66.75%) followed by β-Pinene (13.92%) and γ-Terpinene (3.10%). In both DPPH scavenging and bleachability of β-carotene in linoleic acid system assays, the essential oil extract exhibited the highest activity compared to the Tocoblend. Tests conducted at pilot scale showed that the margarine elaborated with essential oil extract was more resistant to oxidation than the margarine reference with Tocoblend. In addition, the physicochemical properties were not modified.